2000
DOI: 10.1143/jjap.39.l611
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Crystallization in an Amorphous Metal during Shear Deformation

Abstract: A molecular dynamics simulation was performed to investigate the structural changes during a shear deformation process in an amorphous metal. An amorphous model is constructed from Ni atoms interacting via a Morse-type pairwise additive potential. At shear stresses below 2.4 GPa, shear strain increased linearly with increasing shear stress. However, large shear deformation occurred when shear stress reached 2.8 GPa. During this shear deformation, crystallization was observed in the model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…This crystallographic orientation relationship agreed well with our molecular dynamics ͑MD͒ study of crystallization during deformation in a Ni amorphous metal. 10 This morphology is clearly different from those precipitated by annealing. Sui reported that the crystals precipitated by heating of a Ni-11.3 wt %P amorphous alloy had a random orientation relationship with one another.…”
Section: Control Of Nanocrystalline Orientation Using the Applicationmentioning
confidence: 83%
“…This crystallographic orientation relationship agreed well with our molecular dynamics ͑MD͒ study of crystallization during deformation in a Ni amorphous metal. 10 This morphology is clearly different from those precipitated by annealing. Sui reported that the crystals precipitated by heating of a Ni-11.3 wt %P amorphous alloy had a random orientation relationship with one another.…”
Section: Control Of Nanocrystalline Orientation Using the Applicationmentioning
confidence: 83%
“…[19][20][21] Further, it is known that the copper type texture that we observe in YSZ occurs in certain fcc metals after cold deformation. It is thought that this texture is at least partly due to slipping of crystal planes and crystallite rotation during deformation.…”
mentioning
confidence: 57%
“…Additional insight can be gained from molecular-dynamic simulations. An orientation relationship was observed for the shear-and crystallographic direction of deformationinduced Ni nanocrystals (Tarumi et al, 2000). …”
Section:  mentioning
confidence: 92%